Enhancing nutrient removal in bioretention cells: a citywide feasibility and effectiveness study - Cipra, Mattheu, author; Arabi, Mazdak, advisor; Sharvelle, Sybil, committee member; Bousselot, Jennifer, committee member (Colorado State University. Libraries, 2025)
In 2013, the City of Fort Collins (the City) adopted new stormwater management criteria that encouraged the use of low-impact development (LID) practices, particularly those that promoted filtration and infiltration. As a result of these new criteria, the use of bioretention cells (BRCs), along with other LID technologies, became increasingly common among new developments. However, a field study conducted by the City from 2013 through 2015 observed poor nutrient removal in a newly constructed BRC, prompting further investigations into strategies to enhance nutrient removal. In addition to altering bioretention soil media mix designs, subsequent studies conducted by the City identified two retrofits to enhance the nutrient removal capabilities of existing BRCs: (1) a 0.5-inch surface application of Aluminum Water Treatment Residuals (Al-WTRs); and (2) modifying underdrain systems—with an upturned elbow or vertical riser—with the intent of expanding internal water storage zones (IWSZs) by 6 inches. Amending BRCs with Al-WTRs enhances phosphorus removal, while increasing IWSZs promotes nitrogen removal by supporting denitrification. This study identified 230 existing BRCs across the City, of which, 212 had sufficient documentation to support the development of hydrologic models to evaluate the potential impacts of the proposed retrofits. Ultimately, retrofitting BRCs with Al-WTRs would require 443.34 cubic yards of Al-WTRs and would reduce annual effluent total phosphorus (TP) loads by 46.9% (from 223.26 to 118.57 lbs./yr), while total nitrogen (TN) loads would remain unaffected (1,318.41 lbs./yr). Should BRCs only receive the underdrain retrofit, TP and TN annual effluent loads would be reduced by 2.8% (from 223.26 to 217.09 lbs./yr) and 15.49% (from 1,318.41 to 1,114.25 lbs./yr), respectively. Lastly, combining the two proposed retrofits will further enhance TP reductions to 47.8% (from 223.26 to 116.58 lbs./yr), while TN load reductions will remain at 15.49%. Traditionally, Al-WTRs are disposed of in landfills as they are a waste byproduct from the coagulation-flocculation process at drinking water treatment plants. Repurposing 443.34 cubic yards of Al-WTRs will save the City $17,300 in landfill dumping fees. Unfortunately, these savings do not offset the estimated $40,400 cost associated with retrofitting BRCs with Al-WTRs. Additionally, modifying all existing BRC underdrain systems is estimated to cost $87,500. As a result, the City would need to allocate funds to enhance the nutrient removal capabilities of existing BRCs. Lastly, two Multi-Criteria Decision Analyses were conducted—one for each proposed retrofit—evaluating water quality, economic, and ease of implementation metrics. Using City-assigned measures of importance, two lists were developed to inform the City which BRCs should be prioritized first in future retrofit efforts.
Keywords: bioretention cells; nutrient reductions; internal water storage zones; aluminum water treatment residuals